2001
DOI: 10.1203/00006450-200108000-00012
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-β Receptor Expression in the Dorsocaudal Brainstem Parallels Hypoxic Ventilatory Depression in the Developing Rat

Abstract: The temporal trajectory of platelet-derived growth factor (PDGF)-␤ receptor activation within the dorsocaudal brainstem parallels that of the mild hypoxic ventilatory depression (HVD) seen in adult rats. We hypothesized that enhanced PDGF-␤ receptor activity may account for the particularly prominent HVD of developing mammals. To study this issue, 2-, 5-, 10-, and 20-d-old rats underwent hypoxic challenges (10% O 2 for 30 min) after pretreatment with either vehicle (Veh) or the selective PDGF-␤ receptor antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Since previous reports have shown that PDGFR-β is expressed in the cortex, hippocampus, amygdala, and brainstem [5], [3], [65], PDGFR-β deletion may result in a decrease in the long-term synaptic plasticity of various brain regions. Consistent with this concept, recent studies have reported that PDGF-B is important for long-term potentiation (LTP) in the hippocampus of mice and regulates expression of Arc/Arg3.1 , a gene that has been implicated in synaptic plasticity and LTP [66], and that LTP is disturbed in the hippocampus of the PDGFR-β KO mice [67].…”
Section: Discussionmentioning
confidence: 99%
“…Since previous reports have shown that PDGFR-β is expressed in the cortex, hippocampus, amygdala, and brainstem [5], [3], [65], PDGFR-β deletion may result in a decrease in the long-term synaptic plasticity of various brain regions. Consistent with this concept, recent studies have reported that PDGF-B is important for long-term potentiation (LTP) in the hippocampus of mice and regulates expression of Arc/Arg3.1 , a gene that has been implicated in synaptic plasticity and LTP [66], and that LTP is disturbed in the hippocampus of the PDGFR-β KO mice [67].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hypoxia-induced activation of the PDGF-␤ receptor in the CB is temporally associated with activation of an antiapoptotic mechanism via phosphatidylinositol 3-kinase-dependent phosphorylation of both Akt and BAD pathway (38). In addition, activation of PDGF-␤ receptor is an important contributor to hypoxic ventilatory roll-off at all postnatal ages but more critical in developing animals (45). Because prenatal nicotine exposure is associated with modulation of hypoxic ventilatory roll-off, it could lead to perturbation of this important protective mechanism, which may lead to decreased hypoxic tolerance of brain stem neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms proposed include central accumulation and/or release of inhibitory neurotransmitters on respiratory neurons [40]. There is an identified role for protein factors, like PDGF and its receptors, in this response [41][42][43].…”
Section: Time Domain Responses To Hypoxia and Reoxygenationmentioning
confidence: 99%